Analysis of movement patterns by elite male players of beach volleyball - Cortell-Tormo, J. M.; Prerez-Turpin, J. A.; Chinchilla, J. J.; Cejuela, R.; Suarez, C. (Perceptual and Motor Skills, 2011)
The aim of this study was to analyse and compare movement patterns and direction of locomotion in professional men's beach volleyball. A quantitative analysis of beach volleyball play was carried out for 10 players in the European Beach Volleyball Championship 2005. Video recordings were made of the 1,997 movements in 4 matches. Analysis showed that male players used more offensive than defensive movement patterns. Defensive movement patterns were more blocks and defense than receptions. Offensive movement patterns were more attack and placements than attack preparation moves. Advance was the direction of locomotion most used. Identifying and understanding such movement patterns are vital to defining specific, effective training strategies for men's beach volleyball players.